Designing a Ring-VCO for RFID Transponders in 0.18 μm CMOS Process - Jubayer Jalil; Mamun Bin Ibne Reaz; Mohammad Arif Sobhan Bhuiyan; Labonnah Farzana Rahman; Tae Gyu Chang (The Scientific World Journal)
In radio frequency identification (RFID) systems, performance degradation of phase locked loops (PLLs) mainly occurs due to high phase noise of voltage-controlled oscillators (VCOs). This paper proposes a low power, low phase noise ring-VCO developed for 2.42 GHz operated active RFID transponders compatible with IEEE 802.11 b/g, Bluetooth, and Zigbee protocols. For ease of integration and implementation of the module in tiny die area, a novel pseudodifferential delay cell based 3-stage ring oscillator has been introduced to fabricate the ring-VCO. In CMOS technology, 0.18 μm process is adopted for designing the circuit with 1.5 V power supply. The postlayout simulated results show that the proposed oscillator works in the tuning range of 0.5–2.54 GHz and dissipates 2.47 mW of power. It exhibits a phase noise of −126.62 dBc/Hz at 25 MHz offset from 2.42 GHz carrier frequency.